Digital Literacy and Public Policy through the Library Lens - Visser, Marijke (Maine Policy Review, 2013)
Virtually every aspect of our lives now has a digital dimension. Our first interaction with an employer is online; our education occurs online; we collaborate online with colleagues in different countries in real-time; and we keep in touch with friends and family online. It is essential that everyone has the skills necessary to be part of this digital reality. Libraries play a pivotal role in supporting the development of digital literacy skills of their patrons and are a key partner in digital literacy activities in communities across the county.